The Japanese employment system : Adapting to a new economic environment - Rebick, Marcus (Oxford University Press, 2005)
This book examines the evolution of Japan's traditional employment practices-lifetime employment, seniority wages, and enterprise unions-in the face of economic stagnation and globalization. It shows how firms have adapted by introducing more flexible labor arrangements, leading to both continuity and significant change in the Japanese labor market.